Peningkatan Keterampilan Makan pada Anak Down Syndrome melalui Terapi Okupasi Berbasis Sensory Integration: Studi Kasus - Nur Arsyi, Reza; Thresagloria, Tambunan Seselia; Luthfi, Muhammad; K, Ayleen Alicia; Gideon, Hermito (Jurnal Fisioterapi Terapan Indonesia, 2025)
Children with Down Syndrome (DS) frequently experience feeding difficulties due to hypotonia, sensory processing disorder, and oromotor impairments. This case study aimed to describe the clinical reasoning and effectiveness of a sensory integration (SI)-based occupational therapy intervention in improving feeding skills in a 10-year-old child with DS. The intervention consisted of 12 structured sessions focusing on postural stability, proprioceptive awareness, fine motor control, and oromotor coordination. Evaluation tools included Sensory Profile 2 and the Functional Independence Measure (FIM). Post-intervention outcomes indicated significant improvement in spoon use, posture during mealtime, texture tolerance, and self-feeding independence. FIM scores improved from total assistance (score 1) to supervision (score 5). This case highlights the potential of SI-based occupational therapy in enhancing functional feeding independence in children with DS.